Greek mathematics in English: the work of Sir Thomas L. Heath (1861-1940) - Wardhaugh, B (Springer, 2016)
This short note provides some basic information about the life and work of Sir Thomas Little Heath (1861–1940), the author of well-known English versions of ancient Greek mathematical works. It suggests some of the questions which a study of Heath might ask, and provides brief illustrations of some ways in which his work might be situated intellectually and biographically.